2022
DOI: 10.1002/ecm.1513
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of pollen productivity and dispersal: How pollen assemblages in small lakes represent vegetation

Abstract: Quantitative understanding of vegetation dynamics over timespans beyond a century remains limited. In this regard, the pollen-based reconstruction of past vegetation enables unique research opportunities by quantifying changes in plant community compositions during hundreds to thousands of years. Critically, the methodological basis for most reconstruction approaches rests upon estimates of pollen productivity and dispersal. Previous studies, however, have reached contrasting conclusions concerning these estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“… We use the concept pollen dispersal to refer to how far for example airborne pollen grains may travel before being deposited (Yao et al ., 2022). …”
Section: Functional Traits Of Fossil Spores Pollen and Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“… We use the concept pollen dispersal to refer to how far for example airborne pollen grains may travel before being deposited (Yao et al ., 2022). …”
Section: Functional Traits Of Fossil Spores Pollen and Seedsmentioning
confidence: 99%
“…The advantage consists of a rapid germination due to the short rehydration time (Pacini & Hesse, 2012) Terminology used for the six pollen traits (pollen size, shape, apertures, sculptures, dispersal unit, and wall thickness) follows the Palynological Database-PalDat (https://paldat.org) and Halbritter et al (2018). *We use the concept pollen dispersal to refer to how far for example airborne pollen grains may travel before being deposited (Yao et al, 2022).…”
Section: Shape Oblate Prolate Spheroidalmentioning
confidence: 99%
“…Others are process-based proxy system models (Evans et al, 2013) that attempt to represent the processes governing the atmospheric transport and deposition of pollen, such as the REVEALS and LOVE (Sugita, 2007a, c) or STEPPS (Dawson et al, 2019a). Efforts continue to test and refine the parameterizations of these models through paired analyses of pollen assemblages and forest composition at local to landscape scales (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the amount of deforested areas using pollen assemblages in Amazonia is also dependent on the source area of pollen (Liu et al, 2022). Studies in the forest-savanna ecotone areas of Bolivia suggested that anemophilous (wind-dispersed) pollen found in lake sediments may be derived from distances of over 40 km (Whitney et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One parameter that has been lacking, however, is quantifying the extent of deforestation that occurred alongside occupation and cultivation. Using pollen assemblages to quantify past land cover has been successful in temperate ecosystems (Dawson et al, 2019; Gaillard, Sugita, Bunting, Dearing, et al, 2008; Gaillard, Sugita, Bunting, Middleton, et al, 2008; Liu et al, 2022; Prentice, 1988; Sugita, 1993, 2007; Trondman et al, 2015). The only attempt to quantify land cover in Amazonia was performed in the savanna‐forest landscape of Bolivia, which revealed that deforestation was easier to detect in the closed‐canopy rainforests than in the savannas (Whitney et al, 2019).…”
Section: Introductionmentioning
confidence: 99%